(untitled) (Journal of Information Technologies in Education (ITE), 2016)
The article highlights the main results of the study using networking technologies of open systems in training bachelors of computer science. The process of informatization of educational policy in Ukraine as a basis for the introduction of network technologies of open systems in the educational process is considered; the historical background of their formation and development is analyzed; the basic concept for their use in educational theory and practice is uderlined. The possibility of using networking technologies of open systems in the learning process of the first (bachelor) level of higher education in the field of knowledge 0403 "System sciences and cybernetics" training direction 6.040302 "Information *" is defined; the principles fundamentalization and modernization in training bachelors of computer science with the use of these technologies are analyzed. Pedagogical conditions for the learning process of bachelors of computer science in higher education are substantiated; procedural model using networking technologies of open systems in training bachelors of computer science is given; the criteria, indexes and levels of competence of bachelor of computer science in the use of networking technologies of open systems in future professional activity are given; the model of competence of bachelor of computer science in the use of networking technologies of open systems is developed and proved. The basic components of the method of using networking technologies of open systems in teaching bachelors of computer science based on improving the content of discipline "Organizational Informatics" using open networking systems are proved.Recommendations of implementation of networking technologies of open systems for students,teaching staff, university administration and teaching support staff are given.